Le métarécit transhumaniste et les fictions technologiques contemporaines - Julien Cueille (Communication)
The author sets out to resolve a paradox: the presence of myth and fictions in contemporary individualistic societies, commonly described as “disenchanted.” Although the statements are not myths in the traditional sense, they nonetheless belong to the world of myth, to muthos. Those that originate in transhumanism, however, disrupt the mythical schema of transformation and revelation of self by short-circuiting the space of interiority in their denial of finiteness. Other fictions originating in popular culture offer more credible alternatives to that particular pseudo-myth and can be used by subjects to reflect on their confusion.